KONSEP OBJEKTIVITAS DALAM PEMBUATAN LAPORAN KEUANGAN (STUDI KASUS PADA HOME INDUSTRY UD. AR. PUTRA TAHUN 2016-2017) - Yanuarmawan, Dion (Jurnal Ilmiah Akuntansi Indonesia, 2018)
The basic concept of accounting is a variety of concepts that can be standardized in delivering a neat and easy to understand financial statements. The basic concept of accounting is the concept of business entity and cost concept. The concept of cost determines that the property or services obtained must be recorded on the basis of actual costs, and the concept of cost itself is divided into two, namely the concept of measurement units and the concept of objectivity.This type of research is quantitative, used to study in depth about the application of basic concept of objectivity in recording financial statements in UD. AR PUTRA. Secondary data source used is transaction proof data at UD. AR PUTRA which covers the amount of purchase requirement during 2017 and sales data. Population in this research is financial report at UD. AR. PUTRA year 2017. The sample in this research is income statement of Year 2017 at UD. AR PUTRA.The results of the study obtained the details of the needs of 2017 Rp 85,888,333, sales details of 2017 Rp766.647.000, trial balance 2017 Rp 1,162,025,600, total general journal Rp 90.231.200, adjusting journal Rp 17.196.667.Keyword: Basic Concepts of Accounting, Financial Statements, Objectivity